Switchable Mesomorphic Materials Based on the Ferrocene−Ferrocenium Redox System: Electron-Transfer-Generated Columnar Liquid-Crystalline Phases - Deschenaux, Robert; Vilches, Maria-Teresa; Schweissguth, Martin; Levelut, Anne-Marie; Long, Gary J.; Hautot, Dimitri; Luneau, Dominique (My University, 1999)
Oxidation of the non-mesomorphic ferrocene derivative 1 with silver toluene-4-sulfonate gave the ferrocenium derivative 2, which showed a monotropic columnar phase. The latter two-dimensional phase is composed of ribbons, in which derivative 2 is organized into bilayers, and has a centered rectangular symmetry with a = 318.3 Å and c = 94.9 Å. The Mössbauer spectra of the ferrocene derivative 1 yields hyperfine parameters that are typical of these derivatives and are, as expected, virtually independent of temperature. In a similar fashion, the hyperfine parameters of the ferrocenium derivative 2 are typical of these derivatives, but in this case at both 78 and 4.2 K slow paramagnetic relaxation of the magnetic moment associated with the rather well isolated paramagnetic ferrocenium ion is observed. The temperature-dependent magnetic susceptibilities of 2 are in agreement with those expected for weakly interacting ferrocenium cores. No magnetic-field-induced orientation was observed upon cooling the sample from the isotropic phase down to the columnar phase. Ferrocene and ferrocenium are valuable units for the design of liquid-crystalline switches.